2018
DOI: 10.1002/aorn.12277
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Successful Outpatient Joint Arthroplasty Program

Abstract: Many surgical procedures are performed in outpatient settings, and outpatient joint replacements are one of the emerging trends in orthopedics. Rising consumer demand for value-driven health care, new technology, and pain management advancements, and more physicians training in minimally invasive surgical techniques during their residency have driven this change. When a facility is considering the establishment of an outpatient joint arthroplasty program, leaders must take into consideration the outcomes data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…8 However, there are numerous factors to consider in order to succeed in establishing an out-patient programme, including the presence of a clinical nurse specialist, careful patient selection, pre-operative patient education and specialized protocols. 10…”
Section: Discussionmentioning
confidence: 99%
“…8 However, there are numerous factors to consider in order to succeed in establishing an out-patient programme, including the presence of a clinical nurse specialist, careful patient selection, pre-operative patient education and specialized protocols. 10…”
Section: Discussionmentioning
confidence: 99%
“…12 Because many of the primary arthroplasties were performed at outpatient centers and community hospitals, tertiary referral centers across the country have been caring for an increasing number of patients with PJI who underwent index arthroplasty procedures elsewhere. [13][14][15] This study was designed to investigate how such patients with PJI who were transferred were initially triaged and managed at the admitting facility. The results of this study demonstrated that almost all academic medical centers accepted transfer of patients with PJI from other hospitals even if the index arthroplasty procedure was not performed there.…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing number of primary arthroplasties being performed annually, the incidence of revision THA and revision TKA is also expected to increase by 70% and 182%, respectively, by 2030 12. Because many of the primary arthroplasties were performed at outpatient centers and community hospitals, tertiary referral centers across the country have been caring for an increasing number of patients with PJI who underwent index arthroplasty procedures elsewhere 13–15…”
Section: Discussionmentioning
confidence: 99%
“…As a first step, a qualitative needs analysis was performed by reviewing available local resources, surveying practices of a nearby ambulatory surgical centre and conducting a review of all pertinent literature 3 19–25. Pilot cases were performed over a 3-month period to help identify barriers for successful outpatient TJA.…”
Section: Methodsmentioning
confidence: 99%